A comparative study of Text Steganography and Linguistic Steganography - Utama, Sunariya; Din, Roshidi; Mahmuddin, Massudi (2015)
This papers presents classification steganography method on text domain based on the perspective of researchers effort in last decade. Tharefore, It has been analyzed the categories of method steganography in medium of text; text steganography and linguistic steganography. The main objective on this paper is identifying the representative those two methods in order to discern the comparison based on technique used in previous study. Specifically, the explication techniques of text steganography consist of word-rule based and featurebased is critical concern in this paper. It has been found the impression categories as comparison of development specific steganography technique.